Permeability of Metformin across an In Vitro Blood-Brain Barrier Model during Normoxia and Oxygen-Glucose Deprivation Conditions: Role of Organic Cation Transporters (Octs) - Sejal Sharma; Yong Zhang; Khondker Ayesha Akter; Saeideh Nozohouri; Sabrina Rahman Archie; Dhavalkumar Patel; Heidi Villalba; Thomas Abbruscato (MDPI AG, 2023)
Our lab previously established that metformin, a first-line type two diabetes treatment, activates the Nrf2 pathway and improves post-stroke recovery. Metformin's brain permeability value and potential interaction with blood-brain barrier (BBB) uptake and efflux transporters are currently unknown. Metformin has been shown to be a substrate of organic cationic transporters (Octs) in the liver and kidneys. Brain endothelial cells at the BBB have been shown to express Octs; thus, we hypothesize that metformin uses Octs for its transport across the BBB. We used a co-culture model of brain endothelial cells and primary astrocytes as an in vitro BBB model to conduct permeability studies during normoxia and hypoxia using oxygen-glucose deprivation (OGD) conditions. Metformin was quantified using a highly sensitive LC-MS/MS method. We further checked Octs protein expression using Western blot analysis. Lastly, we completed a plasma glycoprotein (P-GP) efflux assay. Our results showed that metformin is a highly permeable molecule, uses Oct1 for its transport, and does not interact with P-GP. During OGD, we found alterations in Oct1 expression and increased permeability for metformin. Additionally, we showed that selective transport is a key determinant of metformin's permeability during OGD, thus, providing a novel target for improving ischemic drug delivery.